Determining the tracheal tube size by echography - Hector R Diaz Aguila (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
In this paper we described the importance and how is performed the echography for measuring the diameter of trachea for determining the proper tracheal tube size before intubation.